Vegetative and electrical disorders in women with chronic coronary syndrome depending on the state of bone mineral density - Mykhailovska, N. S.; Stetsiuk, I. O.; Михайловська, Наталія Сергіївна; Стецюк, Ірина Олегівна (Запорізький державний медичний університет, 2022)
Aim: to determine the features of heart rate variability and electrical changes in the myocardium in women with chronic coronary syndrome, depending on the state of the bone mineral density (BMD). Materials and methods. 121 women with chronic coronary syndrome (CCS): stable exertional angina of II–III functional class (FC) (mean age 68.0 (60.0; 75.0) years) were examined and divided into 3 groups: group 1 − 30 women with ССS and normal BMD; group 2 – 33 women with CCS and osteopenia (OPе); group 3 – 58 women with CCS and osteoporosis (OP). All patients underwent daily ECG monitoring and ultrasound osteodensitometry. Results. In women with CCS and OP, increase in the frequency (by 2.9 times; P < 0.05) and duration (by 2.3 times; P < 0.05) of tachycardia episodes, the frequency of registration of ventricular and supraventricular extrasystole episodes (by 8.1 time and 1.2 times, respectively; P < 0.05) if compared to patients without BMD disorders was found. In women with СCS and OPе there was a tendency to increase in these indicators, which did not reach the level of statistical significance. The presence of BMD disorders in patients with CCS was accompanied with decrease in total HRV activity (RMSSD and HRVT), the development of the predominance of ANS sympathetic domain activity, as evidenced by an increase in LF by 44.3 % at the daytime and 44.0 % at night, decrease in HF 2.3 times during the day and 2.1 times at night in patients with OPe and OP, respectively. According to the correlation analysis data, the presence of correlations between the state of BMD and indicators of electrical and autonomic activity of the myocardium was established. Conclusions. In postmenopausal women with CCS, the severity of autonomic and electrical disorders is associated with the degree of bone disorders and is maximal in osteoporosis. Мета роботи – визначити особливості варіабельності серцевого ритму й електричні зміни міокарда в жінок із хронічним коронарним синдромом (ХКС) залежно від мінеральної щільності кісткової тканини (МЩКТ). Матеріали та методи. Обстежили 121 жінку з ХКС: стабільною стенокардією напруження ІІ–ІІІ функціонального класу віком 68,0 (60,0; 75,0) року. Пацієнток поділили на 3 групи: 1 – 30 жінок із ХКС і нормальними показниками МЩКТ; 2 – 33 особи з ХКС та остеопенією (ОПе); 3 – 58 хворих на ХКС та остеопороз (ОП). Усім обстеженим виконали добовий моніторинг ЕКГ, а також ультразвукову остеоденситометрію. Результати. У жінок із ХКС та ОП виявили збільшення частоти (у 2,9 раза; р < 0,05) та тривалості (у 2,3 раза; р < 0,05) епізодів тахікардії, частоти реєстрації шлуночкової та надшлуночкової екстрасистолії (у 8,1 раза та 1,2 раза відповідно; р < 0,05) порівняно з пацієнтами без порушень МЩКТ. У жінок із ХКС та ОПе визначили тенденцію до підвищення названих показників, що не досягла статистичної значущості. Порушення МЩКТ у хворих на ХКС супроводжувалися зменшенням загальної активності ВСР (RMSSD і HRVT), а також переважанням активності симпатичного домену ВНС, підтверджене збільшенням LF на 44,3 % вдень і на 44,0 % вночі, зниженням HF в 2,3 раза вдень і в 2,1 раза вночі у пацієнтів з ОПе та ОП відповідно. У результаті кореляційного аналізу виявили зв’язок стану МЩКТ з індикаторами електричної та вегетативної активності міокарда. Висновки. У жінок із ХКС у постменопаузальному періоді вираженість вегетативних та електричних порушень асоціюється зі ступенем кісткових порушень та є максимальною при остеопорозі.
Вегетативні й електричні порушення в жінок із хронічним коронарним синдромом залежно від стану мінеральної щільності кісткової тканини
Mykhailovska N. S.- ORCID ID: 0000-0001-6781-9406; Stetsiuk I. O. - ORCID ID: 0000-0002-3698-0181.
Keywords: chronic coronary syndrome; osteopenia; osteoporosis; disorders of the autonomic nervous system; arrhythmia; хронічний коронарний синдром; остеопенія; остеопороз; розлади вегетативної нервової системи; порушення ритму